Role of Cytokines in Pathogenesis of Rheumatoid Arthritis - Minda, Vidit (International Journal of Pharmaceutical & Biological Archive, 2018)
Rheumatoid arthritis has multi factorial pathogenesis synovial hyperplasia and joint deformation is a striking characteristic of RA patients. The synovium thickens, and the joint becomes swollen and painful. In arthritis, macrophages accumulate in the synovial membrane and at the cartilage-pannus junction. Macrophages can be activated by several factors expressed in arthritic joint. Neutrophil normally function as a first line of defence against invading pathogens. In a joint affected by RA, neutrophils are the most abundant cellular infiltrators constituting about 90% of the cells found in synovial fluid. Cytokines are small, short-lived proteins that have a key role in integrating responses to a variety of stimuli in immune and inflammatory processes. Binding of their cognate receptors on target cells is followed by activation of enzymes involved in a variety of intracellular signalling cascades that ultimately modulate the genetic cellular response to the particular ligand.